A mutation in thyroid hormone receptor beta causing "resistance to thyroid hormone" in a neonate - (:unkn) unknown (My University, 2010)
Resistance to thyroid hormone (RTH) is an Inherited syndrome characterized by reduced tissue responsiveness to thyroid hormones. The main defects are due to mutations In thyroid hormone receptor beta (TRbeta). A male, term neonate was admitted because of Indirect hyperbilirubinemla and polycythemla. Physical examination revealed ophtalmopathy. High serum T4 with unsupressed thyroid stimulating hormone (TSH) levels suggested RTH. In this presented case, A317T mutation was detected on exon 9 of the TRβ-1 gene and precise diagnosis had been confirmed with genetic testing. In neonates and Infants exhibiting hypo or hyperthyroldism features with increased circulating levels of thyroid hormones with a normal or increased serum TSH concentration should raise the suspicion of RTH.
Keywords: Infant, newborn; Receptors, thyroid hormone; Thyroid hormone resistance syndrome